How do residential burglars select target areas? A new approach to the analysis of criminal location choice - Bernasco, Wim (The British journal of criminology, 2005)
This paper introduces the discrete spatial choice approach to the study of criminal target choice. The approach is used to assess whether residential burglars are attracted to target areas that are affluent, accessible, and poorly guarded. In addition, the importance of these criteria is postulated to vary across burglars. The theory is tested using data on 548 residential burglaries, committed by 290 burglars from the city of The Hague, the Netherlands. The likelihood of a neighbourhood's being selected for burglary is heightened by its ethnic heterogeneity, its percentage of single-family dwellings, and its proximity to where the offender lives. The results and prospects of the discrete spatial choice approach for spatial target selection research are discussed